Exploring Animation Film Media for Better Writing Ability in Indonesian Higher Education EFL Context - Hermi Zaswita; Meladina Meladina (Fakultas Sastra - Universitas Muslim Indonesia, 2021)
This research was oriented by the low ability of students in writing narrative text. For that we need the latest media that can increase students' creativity in thinking in the current technology era so that their writing ability can be better, one of that is animation film. The purpose of this study was to determine the extent to which animated film can make students 'writing ability better and what aspects influence the students' ability to write narrative text through the use of animated film. This research is a Classroom Action Research (CAR) which was conducted third semester students of English education Program in STKIP Muhammadiyah Sungai Penuh. The research was conducted in two cycles, the instruments used were writing tests and observation sheets. The results showed that the students' ability in writing showed significant results in the second cycle with an average of 78.9. From the research, it was also obtained four aspects that affect the improvement of students' writing ability, namely classroom management, classroom activities, learning methods, and material aspects.